Pendampingan Tahfiz Menggunakan Metode Tasmi’ Melalui Program Ekstrakulikuler di SMA 2 Padang - Anita Sarmila; Martin Kustanti; Rezki Amelia; Gusmirawati Gusmirawati (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2024)
This mentoring aims to help students memorize and maintain memorization of the verses of the Qur'an in the Tahfidz extracurricular program at SMA 2 Padang using the tasmi' method. The tasmi' method is a method of memorizing the Qur'an by the teacher listening to the reading of the verses of the Qur'an from students, so that with this tasmi' a memorizer of the Qur'an will be known his shortcomings when submitting memorization, because students can make mistakes in pronouncing letters or harakat. With tasmi' students will be more concentrated in memorizing. This mentoring is carried out using the PAR (Participatory Action Research) method with stages of mentoring, namely the first preparation, the second implementation stage, the third evaluation stage, which later the results of the participants' memorization will be tested and when the results of the exam are sufficient, the students will graduate. The success of the tahfiz mentoring using the TASMI' method is marked by the increasing quality of memorization and reading of students where they graduated above 1 juz, 10 juz and there were even students who graduated 22 juz.